Reliability of the radiographic views in supine position for evaluation of displaced midshaft clavicle fracture length - Pinkawas Kongmalai; Peeraput Chiaprasert; Visit Rungsinaporn (Journal of Orthopaedic Surgery, 2020)
Purpose: To analyze the agreement of the displaced midshaft clavicle fracture length measurement between each of the supine radiographic position (chest anteroposterior (AP), both clavicle AP, and 20° cephalic tilt clavicle AP view) and computed tomography (CT) scan of the clavicle. Furthermore, the inter- and intraobserver reliability of each radiographic position was analyzed. Methods: Prospective cross-sectional study was performed with patients diagnosed with displaced midshaft clavicle fracture treated conservatively. Three views of radiographs and CT scan of clavicle were obtained in supine position after informed consent. The measurement of fractured clavicle length was done by three observers at the time and after 4 weeks interval. Results: Thirty-three patients (25 males and 8 females), with a mean age of 45, were recruited. The agreement between each of the radiographic measurement and CT scan was good. The interobserver reliability was moderate to good for radiographic measurement. The highest intraclass correlation coefficient (ICC) of 0.80–0.81 was shown between the 20° cephalic tilt and the CT scan, followed by the both clavicle AP (0.75–0.77) and the chest AP (0.69–0.75), respectively. There was an excellent intraobserver reliability for all of the radiographic measurement with the ICC 0.92–0.99. Conclusion: The supine radiographs could be a useful option to measure the displaced midshaft clavicle fracture length. The recommended view was the 20° cephalic tilt clavicle AP view in supine position to best evaluate the fractured clavicle length.